2014
DOI: 10.1016/j.sbspro.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Service Quality Dimensions on Patient Satisfaction, Repurchase Intentions and Word-of-Mouth Communication in the Public Healthcare Industry

Abstract: The aims of this study are investigating the effect of service quality (SQ) dimensions on satisfaction, identifying the effect of satisfaction on word of mouth (WOM) communication and repurchase intention (RI) and searching a significant relationship between WOM and RI. Improving CS and delivering SQ help service providers to differentiate the offering. Thus our motive is to find out that the statement is true for healthcare industry. This study has adopted the work of Parasuraman et al.'s SERVQUAL variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
177
1
36

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(240 citation statements)
references
References 61 publications
26
177
1
36
Order By: Relevance
“…Furthermore, the service quality dimension of tangibles was found to be the only service quality dimension to have a significant relative influence on patient satisfaction. This is contrary to studies that found the responsiveness, empathy, and assurance dimension contributes more to patients' satisfaction (Essiam, 2013;Kitapci et al, 2014). While these are studies based on overall hospital services, this study focused on services rendered by the health information management department.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the service quality dimension of tangibles was found to be the only service quality dimension to have a significant relative influence on patient satisfaction. This is contrary to studies that found the responsiveness, empathy, and assurance dimension contributes more to patients' satisfaction (Essiam, 2013;Kitapci et al, 2014). While these are studies based on overall hospital services, this study focused on services rendered by the health information management department.…”
Section: Discussionmentioning
confidence: 70%
“…Also, a study revealed a positive and significant relationship between hospital service quality and the five dimensions of SERVQUAL (Kazemi, Ehsani, Abdi, & Bighami, 2013). On the other hand, a survey found empathy and assurance to be positively related to patients' satisfaction in a Turkish hospital (Kitapci, Akdogan, & Dortyol, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…If the customer is satisfied with a product or service, he or she will recommend it to others and if the customer is unhappy about his or her experience, he or she will spread a negative word about it. The former is known as positive word of mouth and the later as negative word of mouth (Kitapci, Akdogan, & Dortyol, 2014).The desire to maintain a long-term relationship by the way of commitment to purchase from the same provider is known as repurchase intention. It is an individual's dedication of keeping alive the connection with a service provider and buying the next product or service from the same one (Kitapci et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The former is known as positive word of mouth and the later as negative word of mouth (Kitapci, Akdogan, & Dortyol, 2014).The desire to maintain a long-term relationship by the way of commitment to purchase from the same provider is known as repurchase intention. It is an individual's dedication of keeping alive the connection with a service provider and buying the next product or service from the same one (Kitapci et al, 2014). Figure 1 is describing the conceptual framework developed for this research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the service line, responsivness is also defined as one's willingness to assist customer and provide quick service (Brady & Cronin, 2001;Ismail & Mohd Yunan, 2016;Kitapci, Akdogan, & Dortyol, 2014). Daugherty, Ellinger, and Rogers (1995), and Moyes, Cano-Kourouklis, and Scott (2016) found that responsiveness to customers is needed to build and sustain long term relationship with the customers.…”
Section: Responsivenessmentioning
confidence: 99%